Non-matching meshes data transfer using Kriging model and greedy algorithm. (July 2018) - Yang, Fan; Yue, Zhufeng; Lu, Tian Jian
Highlights: The Kriging model is used for data transfer on non-matching meshes. The greedy algorithm is used to increase the accuracy and the efficiency of the Kriging model. A learning function is introduced to guide for picking out the samples adaptively. Abstract: The domain decomposition is a conventional approach to compute complex multidisciplinary simulations. The data transfer must be performed on their common interface due to the non-matching meshes for different domains. The adaptive Kriging interpolation method is proposed based on the greedy algorithm. By introducing a learning function, the Kriging interpolation model is constructed by the source grid values. In this way, part of the total source points are selected and the Kriging model is of high precision for the data transfer between the interface. Four examples are investigated to demonstrate the efficiency and accuracy of the proposed method.